Maltrato infantil: normatividad y psicología forense (2010)
The following documentary, pedagogical paper, is addressed to professionals who work with abused children. It introduces the reader to the current legal framework and presents the institutions in charge of protecting and attending abused children, besides the psychological forensic assessment instruments. The contribution of the Legal Psychology to proof psychological damage is presented. Finally, it is proposed to appeal to less punitive alternative mechanisms, specifically to the mechanisms of the restorative justice.